The complex act of projecting oneself into the future. Issue 1 (8th November 2012) - Klein, Stanley B.
Abstract: Research on future‐oriented mental time travel (FMTT) is highly active yet somewhat unruly. I believe this is due, in large part, to the complexity of both the tasks used to test FMTT and the concepts involved. Extraordinary care is a necessity when grappling with such complex and perplexing metaphysical constructs as self and time and their co‐instantiation in memory. In this review, I first discuss the relation between future mental time travel and types of memory (episodic and semantic). I then examine the nature of both the types of self‐knowledge assumed to be projected into the future and the types of temporalities that constitute projective temporal experience. Finally, I argue that a person lacking episodic memory should nonetheless be able to imagine a personal future by virtue of (1) the fact that semantic, as well as episodic, memory can be self‐referential, (2) autonoetic awareness is not a prerequisite for FMTT, and (3) semantic memory does, in fact, enable certain forms of personally oriented FMTT. WIREs Cogn Sci 2013, 4:63–79. doi: 10.1002/wcs.1210 This article is categorized under: Psychology > Memory